Pure red cell aplasia among ABO mismatched hematopoietic stem cell transplant recipients: a 13-years retrospective study and literature review - Metafuni, Elisabetta; Busnego Barreto, Maria Teresa; Valentini, Caterina Giovanna; Giammarco, Sabrina; Limongiello, Maria Assunta; Sorà, Federica; Bianchi, Maria; Massini, Giuseppina; Piccirillo, Nicola; Putzulu, Rossana; Frioni, Filippo; Bacigalupo, Andrea; et al. (Frontiers in Oncology, 2024)
Background: Pure red cell aplasia (PRCA) is a possible complication after allogeneic hematopoietic stem cell transplantation (HSCT) with major ABO incompatibility. Patients experience delayed engraftment of the erythroid series, with prolonged transfusion-dependent anemia and iron overload. Methods: We performed a revision of the most recent literature about post-HSCT PRCA treatment procedures. Moreover, we conducted a retrospective study, over the last 13-years, which included all consecutive major ABO mismatched HSCT performed in our unit, with the aim to assess PRCA incidence, risk factors, and response to different treatments. Overall, 194 patients received a major ABO mismatched transplant from 2010 to 2022. For each patient, data about demographic and transplant characteristics, engraftment, blood transfusion, and possible treatment received were collected. Results: The literature review returned 23 eligible papers on PRCA treatment, with high success rate using plasma-exchange (PEX) and immunoadsorption procedures, daratumumab, and eltrombopag. Our study identified a total of 24 cases of PRCA. Among risk factors for PRCA development, we have found older recipient age (p=0.01), high pre-HSCT IgG and IgM IHA titer (p<0.0001), major rather than bidirectional ABO incompatibility (p=0.02), low T CD8 lymphocyte count in the graft (p=0.006), relative donor (p=0.02) and bone marrow as stem cell source (p=0.002). However, multivariate analysis confirmed only pre-HSCT IgG IHA titer as the unique risk factor for PRCA occurrence. The optimal cut-off value of pre-HSCT IgG IHA for PRCA development, and it resulted to be 1/64, with a 100% sensitivity and 68.8% specificity (p<0.0001). All patients with PRCA had received rhEPO and transfusion support and 20 patients received additional treatments like PEX, rituximab, and more recently daratumumab. Comprehensively, PEX and rituximab obtained a response in half of the cases, at a variable time, while the few cases of patients we treated with daratumumab suggest promising results. The overall response rate in our cohort was 75%, with significantly better survival (94.4% vs. 16.7%) and lower transplant-related mortality (6.3% vs. 80%) for PRCA responders. Conclusions: Standardized guidelines on when and how to treat PRCA are necessary because the current treatment is controversial among centers.